Operando and three-dimensional visualization of anion depletion and lithium growth by stimulated Raman scattering microscopy - Cheng, Qian; Wei, Lu; Liu, Zhe; Ni, Nan; Sang, Zhe; Zhu, Bin; Xu, Weiheng; Chen, Meijie; Miao, Yupeng; Chen, Long-Qing; Min, Wei; Yang, Yuan (Nature communications, 2018)
Visualization of ion transport in electrolytes provides fundamental understandings of electrolyte dynamics and electrolyte-electrode interactions. However, this is challenging because existing techniques are hard to capture low ionic concentrations and fast electrolyte dynamics. Here we show that stimulated Raman scattering microscopy offers required resolutions to address a long-lasting question: how does the lithium-ion concentration correlate to uneven lithium deposition? In this study, anions are used to represent lithium ions since their concentrations should not deviate for more than 0.1 mM, even near nanoelectrodes. A three-stage lithium deposition process is uncovered, corresponding to no depletion, partial depletion, and full depletion of lithium ions. Further analysis reveals a feedback mechanism between the lithium dendrite growth and heterogeneity of local ionic concentration, which can be suppressed by artificial solid electrolyte interphase. This study shows that stimulated Raman scattering microscopy is a powerful tool for the materials and energy field. The relationship between Li-ion concentration and Li deposition remains an issue to be addressed. Here the authors show that stimulated Raman scattering microscopy offers insight into the concentration evolution and its impact on the dendrite growth, which is not possible by existing techniques.